Comparative study on driver mutations in primary and metastatic melanomas at a single Japanese institute: A clue for intra- and inter-tumor heterogeneity. Issue 1 (January 2017) - Kaji, Tatsuya; Yamasaki, Osamu; Takata, Minoru; Otsuka, Masaki; Hamada, Toshihisa; Morizane, Shin; Asagoe, Kenji; Yanai, Hiroyuki; Hirai, Yoji; Umemura, Hiroshi; Iwatsuki, Keiji
Highlights: In the present paper, we analyzed driver mutations of 77 melanoma tissue samples from 60 patients. We focused on the intra-tumor mutational　heterogeneity in the primary melanoma. Furthermore, we focused on the inter-tumor mutational heterogeneity between the primary and metastatic melanomas. Abstract: Background: Searching for driver mutations in melanoma is critical to understanding melanoma genesis, progression and response to therapy. Objectives: We aimed to investigate the frequency and pattern of driver mutations in Japanese primary and metastatic melanomas including cases of unknown primary origin, in relation to their clinicopathologic manifestations. Methods: Seventy-seven samples from 60 patients with melanoma were screened for 70 driver mutations of 20 oncogenes by Sequenom MelaCarta MassARRAY, and the results for primary and metastatic melanomas were compared. Results: Of 77 tissue samples, BRAF V600E was detected in 21 samples (27%), CDK4 R24C in 7, EPHB6 G404S in6, BRAF V600 K in 2, NEK10 E379 K in 2, and CDK4 R24H, NRAS Q61 K, NRAS Q61R, KRAS G12A, KIT L576P, KIT V559A, ERBB4 E452 K, and PDGFRA E996 K in one sample each. No driver mutations related to the MAPK cascade including RAS and BRAF were detected in the chronically sun-damaged (CSD) group of melanoma. Dual or triple driver mutations were found in four of 40 (10%) samples from the primary melanomas, and three of 37 (8%) of the metastatic melanomas. Fourteen of 26 (54%) samples of non-CSD melanoma, and 3 of 6 (50%) melanomas of unknown primary origin had the BRAF V600E mutation. Mutations in membrane-bound receptors including KIT, ERBB4 and EPHB6 were detected in 8 of 77 (10%) samples. Of 17 pairs of primary and metastatic melanomas from the same patient, the primary mutation pattern was changed to a novel one in three cases, and only one of the plural mutations in the primary melanoma was found in the metastatic lesions in two cases. Conclusions: BRAF V600E is a predominant mutation in non-CSD melanoma and melanomas of unknown primary origin. Mutational heterogeneity may exist in the primary melanoma (intra-tumor heterogeneity), and between the primary and metastatic lesions (inter-tumor heterogeneity).